(untitled) (FACTUM: Jurnal Sejarah dan Pendidikan Sejarah, 2025)
This article explores the history of friendship and strong diplomatic relations between two prominent world leaders: President Sukarno of Indonesia and President Kim Il Sung of North Korea. Their close relationship reached its peak during Sukarno’s presidency, particularly during Indonesia’s Guided Democracy era. Both leaders made reciprocal visits to each other’s countries, further solidifying bilateral ties. This closeness is reflected in cultural symbols such as the North Korean song “Bung Karno” and the naming of the orchid species Kimilsungia. The article employs the historical method, which includes the stages of heuristics, verification, interpretation, and historiography. It draws on both primary and secondary sources, including photographic archives from the University of Indonesia, newspapers, books, theses, journals, and scholarly works related to the topic. This research aims to contribute to the historiography of diplomatic history between Indonesia and North Korea, a subject that remains relatively underexplored.